2013
DOI: 10.26719/2013.19.8.704
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use among Iranian dental students: a national survey

Abstract: A national survey was conducted to provide up-to-date data on current and ever use of tobacco among Iranian dental students. All 4th-year students of 8 randomly selected dental schools were surveyed anonymously in December 2010 using the Global Health Professions Student Survey questionnaire. Of 325 participants, 54.2% were ever users of tobacco products (73.0% of males versus 44.4% of females); 50.8% had used waterpipes, 34.2% cigarettes and 9.3% other products. The most common age at first use was 20-24 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 20 publications
7
13
2
Order By: Relevance
“…In national surveys, the prevalence of smoking is reported to be 17.4% in Iranian students (23), 8.5% in 16 to 25-year-old young people [24], and 18.3% in males and 1.3% in females in the age group of 19-49 years [25]. Smoking rates reported were signi cantly more prevalent in males than females, which is similar to the ndings of previous studies in Iranian senior dental students [22,26], oral health professionals [6], and Iranian general population [25]. This can be a result of less social acceptance of women's smoking in Iran, or their better health consciousness.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In national surveys, the prevalence of smoking is reported to be 17.4% in Iranian students (23), 8.5% in 16 to 25-year-old young people [24], and 18.3% in males and 1.3% in females in the age group of 19-49 years [25]. Smoking rates reported were signi cantly more prevalent in males than females, which is similar to the ndings of previous studies in Iranian senior dental students [22,26], oral health professionals [6], and Iranian general population [25]. This can be a result of less social acceptance of women's smoking in Iran, or their better health consciousness.…”
Section: Discussionsupporting
confidence: 84%
“…As also reported in a previous study (22), the smoking rate among senior dental students was reported higher than that among the Iranian general population. In national surveys, the prevalence of smoking is reported to be 17.4% in Iranian students (23), 8.5% in 16 to 25-year-old young people [24], and 18.3% in males and 1.3% in females in the age group of 19-49 years [25].…”
Section: Discussionsupporting
confidence: 81%
“…Tobacco consumption among the fourth-year Iranian dental students was 54.2%, 73.0% of them were males, whereas 44.4% were females; 50.8% were smoking waterpipes, 34.2% cigarettes, and 9.3% were using other tobacco products. 15 In the present study, 37.96% of all participants were smokers. The finding of male smoker preponderance is in line with previous reports.…”
Section: Discussionmentioning
confidence: 41%
“…In the same study, current tobacco use was reported by 20.6% of respondents, cigarette smoking by 10.8%, and water pipe smoking by 15.8%. [4] Non-users of tobacco as well as alcohol were more in our study as compared to other studies. In a study conducted by Underwood et al, among 384 dental undergraduates at one English University tobacco smoking was reported by 27% of males and 13.5% of females, 63% of males and 69.5% of females reported drinking alcohol.…”
Section: Graph 1: Sex-wise Distribution In Respect To Tobacco Consumpcontrasting
confidence: 52%